Systematics of Pholidobolus from southern Ecuador, with description of three new species (Squamata, Gymnophthalmidae) - Parra Sotalín, Rommy Vanessa (2019)
We describe three new species of Pholidobolus from southern Ecuador based on morphological and genetic evidence. We infer the phylogenetic position using DNA sequences of mitochondrial and nuclear genes. The phylogeny shows that the new species, Pholidobolus samek sp. n., P. elquimi sp. n. and P. oni sp. n., are nested within the “P. macbrydei” clade. Pholidobolus samek and P. elquimi differ from their congeners by having bright green dorsolateral stripes on the head; whereas P. oni in having small scales between the posterior corner of the orbit and the anterior edge of the external auditory meatus. Pholidobolus samek and P. elquimi occur in Cordillera del Cóndor, a region with few lizard collections. Our results allowed us to confirm that P. macbrydei, as currently defined, is a species complex that includes three new species described herein and four candidate species. These discoveries reveal high levels of diversity within Pholidobolus in southern Ecuador.